1996
DOI: 10.1002/(sici)1097-4547(19960201)43:3<315::aid-jnr6>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between NG2 proteoglycan and PDGF ?-receptor on O2A progenitor cells is required for optimal response to PDGF

Abstract: Previous studies on the NG2 chondroitin sulfate proteoglycan have shown that NG2 is expressed on A2B5‐positive O2A progenitor cells, which are known to respond to platelet‐derived growth factor (PDGF). In the accompanying paper (Nishiyama et al.; J Neurosci Res 43:299–314, 1996) we show that on O2A progenitors in the embryonic and newborn rat brain, NG2 and PDGF α‐receptor display an extensive co‐localization which becomes less pronounced as the brain matures past the first postnatal week. The present communic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
118
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 225 publications
(131 citation statements)
references
References 48 publications
13
118
0
Order By: Relevance
“…The increase in PDGF ␣-receptor mRNA hybridization signal in transgenic corpus callosum and cerebellar medulla, compared to controls, reveals that the increase in cell number is at least in part due to generation of more oligodendrocytes. Staining with antibodies to the proteoglycan NG2, which colocalizes with PDGF ␣-receptor on oligodendrocyte precursors in vitro and in vivo (Nishiyama et al, 1996a(Nishiyama et al, , 1996b, revealed an increase also of NG2 immunoreactivity in MBP-PDGF-B mice, thus confirming these cells as O2A progenitors.…”
Section: Discussionsupporting
confidence: 72%
“…The increase in PDGF ␣-receptor mRNA hybridization signal in transgenic corpus callosum and cerebellar medulla, compared to controls, reveals that the increase in cell number is at least in part due to generation of more oligodendrocytes. Staining with antibodies to the proteoglycan NG2, which colocalizes with PDGF ␣-receptor on oligodendrocyte precursors in vitro and in vivo (Nishiyama et al, 1996a(Nishiyama et al, , 1996b, revealed an increase also of NG2 immunoreactivity in MBP-PDGF-B mice, thus confirming these cells as O2A progenitors.…”
Section: Discussionsupporting
confidence: 72%
“…treatment with anti-NG2 antibody inhibited proliferation of oligodendrocyte progenitors. 43 Subsequently, we showed that, whereas the combined action of FGF2 and PDGF-AA was able to maintain wild type progenitors in their undifferentiated state, NG2 null progenitors began the process of differentiation even in the presence of the two growth factors. 119 More careful work done with aortic smooth muscle cells showed that NG2 null cells failed to proliferate or migrate normally in response to PDGF-AA, due to poor activation of PDGFRα.…”
Section: Cell Proliferationmentioning
confidence: 72%
“…Along with PDGFRα, NG2 has become one of the most reliable markers for these progenitors. 4,[41][42][43][44][45][46] In keeping with general observations regarding NG2 expression, the proteoglycan is not expressed by multipotent neural stem cells in primary and secondary germinal zones of the central nervous system, but is upregulated on progenitors that emerge from these germinal zones and are committed to the oligodendrocyte lineage. Through a program of proliferation and migration, oligodendrocyte progenitors populate the entire central nervous system and differentiate into myelinating oligodendrocytes.…”
Section: Ng2 Expression In the Central Nervous Systemmentioning
confidence: 99%
“…5, 6). PDGFR␣ϩ/NG2ϩ glial progenitors are abundant and widely distributed in the subcortical white matter of adult humans and rodents (Gogate et al, 1994;Nishiyama et al, 1996;Scolding et al, 1998;Dawson et al, 2000). As with our model, human gliomas grow by diffusely infiltrating the brain and the tumor cells intermingle with normal brain cells.…”
Section: Recruitment As a Mechanism Of Glioma Growthmentioning
confidence: 72%